A CENOZOIC SEAWATER SR/CA RECORD FROM BENTHIC FORAMINIFERAL CALCITE AND ITS APPLICATION IN DETERMINING GLOBAL WEATHERING FLUXES - Lear C.H.; Elderfield H.; Wilson P.A. (My University, 2003)
A Cenozoic multi-species record of benthic foraminiferal calcite Sr/Ca has been produced and is corrected for inter-specific offsets (typically less than 0.3 mmol/mol) and for the linear relationship between decreasing benthic foraminiferal Sr/Ca and increasing water depth. The water depth correction, determined from Holocene, Late Glacial Maximum and Eocene paleowater-depth transects, is ~0.1 mmol/mol/km. The corrected Cenozoic benthic foraminiferal Sr/Ca record ranges from 1.2 to 2.0 mmol/mol, and has been interpreted in terms of long-term changes in seawater Sr/Ca, enabling issues related to higher-resolution variability in Sr/Ca to be ignored. We estimate that seawater Sr/Ca was ~1.5 times modern values in the late Cretaceous, but declined rapidly into the Paleogene. Following a minimum in the Eocene, seawater Sr/Ca increased gradually through to the present day with a minimum superimposed on this trend centered in the late Miocene. By assuming scenarios for changing seawater calcium concentration, and using published carbonate accumulation rate data combined with suitable values for Sr partition coefficients into carbonates, the seawater Sr/Ca record is used to estimate global average river Sr fluxes. These fluxes are used in conjunction with the seawater strontium isotope curve and estimates of hydrothermal activity/tectonic outgassing to calculate changes in global average river 87Sr/86Sr through the Cenozoic. The absolute magnitude of Sr fluxes and isotopic compositions calculated in this way are subject to relatively large uncertainties. Nevertheless, our results suggest that river Sr flux increased from 35 Ma to the present day (roughly two-fold) accompanied by an overall increase in 87Sr/86Sr (by ~0 to 0.001). Between 75 and 35 Ma, river 87Sr/86Sr also increased (by ~0.001 to 0.002) but was accompanied by a decrease (two- to three-fold) in river Sr flux.
Keywords: GLOBAL CHANGE; WEATHERING; RIVERS; BENTHIC TAXA; SEAWATER; PALEOCLIMATOLOGY; Paleogene; Cretaceous; Holocene; Miocene; Eocene; Cenozoic::Paleogene; Кайнозой::Неоген::Миоцен; Mesozoic::Cretaceous; Кайнозой::Палеоген; Мезозой::Меловая; Кайнозой::Палеоген::Эоцен; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Holocene; Cenozoic::Neogene::Miocene; Cenozoic::Paleogene::Eocene